A cobertura previdenciária segundo a PNAD contínua: Uma proposta de mensuraç\~ao da proporç\~ao de protegidos entre ocupados e idosos residentes no país - Graziela Ansiliero; Rogério Nagamine Costanzi; Alexandre Zioli Fernandes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– This paper discusses the differences between the Annual Continuous PNAD and the recently discontinued Annual PNAD, both surveys developed by IBGE; the relevant distinctions on the social security dimension between the two surveys; the guidelines and the official methodology adopted for measuring the level of the social security coverage (focusing the social insurance coverage) based upon the microdata of the Annual PNAD; the possibilities and limitations on applying this methodology on the Continuous PNAD and new a methodological approach for measurement the coverage, duly adapted to the scope of the new survey and to the changes introduced by Law no 11.718/2008, which redefined some of the requirements for the legal characterization of the Rural Special Insured of the RGPS. According to the microdata of the Continuous PNAD of 2016 (5th Interview), adjusted by the concept of an expanded occupied population (which extrapolates the official concept of occupied population used in the survey), the coverage rate for the occupied population, between ages 16 and 59, is 73.5% (72.8% among men, 74.5% among women); among the elderly, people aged 60 years or over, the coverage rate would be of 85.4% (89.6% among men, 82.2% among women). When using the official concept of occupied population used in the survey, the coverage rates would be 80% (occupied workers: 74.4% among men, 74.0% among women) and 84.6% (elderly: 89.1% among men, 81.9% among women).
Keywords: H51; H77; I18; 330; social insurance coverage; social protection; Annual Continuous PNAD